Analisis Pengembangan UMKM Keripik Tempe di Desa Tanjung Putus untuk Meningkatkan Kesejahteraan Masyarakat - Fatimah Fatimah; Salman Rasyid Riyadh; Fazlurrasyid Sulaiman Martua Siregar; Fitri Haraya Sirait (Jurnal Pengabdian Masyarakat, 2025)
This study aims to analyze the development of tempe chip micro, small, and medium enterprises (MSMEs) in Tanjung Putus Village as an effort to improve community welfare. Tempe chip MSMEs have significant potential to drive local economic growth, create jobs, and strengthen the household economy of the village community. The research method used was descriptive qualitative, with data collection techniques through observation, interviews, and documentation of business actors and the surrounding community. The results indicate that the development of tempe chip MSMEs is influenced by human resources, raw material availability, government support, and marketing strategies. Despite obstacles such as limited capital and a lack of product innovation, these MSMEs continue to play a significant role in increasing community income. With proper management, training support, and access to capital, the tempe chip MSME in Tanjung Putus Village has the potential to become a sustainable, leading village sector capable of significantly improving the community’s standard of living.